The meaning of Vučedol settlement burial - Durman, Aleksandar (Array, 2004)
In spite of the fact that, along with individual graves, in Vučedol culture collective burials (of two to eight persons) have also been established. The unusual positions in which all of the buried individuals were found, their mutual disposition in collective graves, as well as the unusual attention devoted to the burials, prove that they were not placed in their respective locations randomly but must have been connected with some collective ritual, and that they bear distinct features of human sacrifice.